2011
DOI: 10.3390/md9122809
|View full text |Cite
|
Sign up to set email alerts
|

Aurantoside J: a New Tetramic Acid Glycoside from Theonella swinhoei. Insights into the Antifungal Potential of Aurantosides

Abstract: The chemical investigation of an Indonesian specimen of Theonella swinhoei afforded four aurantosides, one of which, aurantoside J (5), is a new compound. The structure of this metabolite, exhibiting the unprecedented N-α-glycosidic linkage between the pentose and the tetramate units, has been determined through detailed spectroscopic analysis. The four obtained aurantosides have been tested against five fungal strains (four Candida and one Fusarium) responsible of invasive infections in immuno-compromised pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Aurantosides, a group of tetramic acid glycosides, are found characteristically within specimens of theonellids from the Indo-West Pacific (see Matsunaga et al 1991;Wolf et al 1999;Sata et al 1999a;Ratnayake et al 2005;Angawi et al 2011); a single aurantoside has been identified from a non-theonellid sponge (which was identified only to genus). These compounds were named initially for the golden colour of the pigment from which they were isolated (Matsunaga et al 1991), and are indicated commonly as a yellow oil which is soluble in ethanol.…”
Section: Chemotaxonomymentioning
confidence: 99%
“…Aurantosides, a group of tetramic acid glycosides, are found characteristically within specimens of theonellids from the Indo-West Pacific (see Matsunaga et al 1991;Wolf et al 1999;Sata et al 1999a;Ratnayake et al 2005;Angawi et al 2011); a single aurantoside has been identified from a non-theonellid sponge (which was identified only to genus). These compounds were named initially for the golden colour of the pigment from which they were isolated (Matsunaga et al 1991), and are indicated commonly as a yellow oil which is soluble in ethanol.…”
Section: Chemotaxonomymentioning
confidence: 99%
“…Angawi and cols isolated four aurantosides, including a new compound Aurantoside J, from a Indonesian specimen of Theonella swinhoei and tested against C. albicans, C. parapsilosis, C. glabrata, C. tropicalis, and Fusarium solani (Angawi et al, 2011). The results reveal that Aurantoside I exhibited a very good antifungal effect against all the tested strains, especially for Candida.…”
Section: Rhodomela Confervoidesmentioning
confidence: 99%
“…The chemical diversity of the isolated compounds ranges from unusual steroids (exemplified by the 4-methylene sterol theonellasterol [23] and truncated side-chain sulfated steroids [4]), to complex macrocyclic polyketides (as the well-known swinholide A, now a reference compound in the class of actin interacting cell growth inhibitors [5]), polyene derivatives (as aurantosides [6]), and polypeptides/depsipeptides. The biosynthesis of several secondary metabolites of Theonella has been ascribed to symbiotic microorganisms, as in the case of the polyketide onnamide [7] and the polypeptide polytheonamide [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of our long-standing interest for bioactive secondary metabolites from marine invertebrates, we have recently investigated a specimen of T. swinhoei collected off the coasts of Manado (North Sulawesi, Indonesia), which proved to be rich in aurantosides [6] and 4-methylene steroids [18], while polyketide macrolides and peptide-based derivatives were extremely rare if not absent. Remarkably, the chemical analysis of a different specimen of T. swinhoei , collected in the same area as the previous one, exhibited an extremely different secondary metabolite composition.…”
Section: Introductionmentioning
confidence: 99%